(untitled) (ASEAN Engineering Journal, 2023)
The use of solar PV as an alternative to fulfill household-scale electricity needs has begun to be widely developed. However, the problem of investment costs and the location of solar PV placement for household scale is still a challenge in its implementation. The construction model of rooftop solar PV can affect the investment cost and performance of solar PV. In this paper, the triangle model of rooftop solar PV on grid with PLN (PT. Perusahaan Listrik Negara) electricity network is studied in terms of technology and economics to determine the feasibility of implementing 900 VA household-scale power plants. Testing the application of solar PV technology under solar radiation conditions in the city of Surabaya, Indonesia as a case study. Calculation of electricity production, energy savings, energy sales, and energy purchases to determine technological feasibility as well Net Present Value (NPV), Benefit Cost Ratio (BCR), and Payback Period (PP) to determine the level of economic feasibility. The results of the research of 1,5 KWP (kilowatt peak) solar PV technology on a household scale are able to meet energy needs and reduce PLN electricity purchases to 0% and can sell electrical energy by 13.96% / year of the total electrical energy produced. In addition, the NPV, BCR with a value greater than zero, and PP of 8.6 is less than 15 years which is the service life of solar PV, so solar PV/ PLN on grid is feasible to be implemented for household scale power generation models.